SILENT WITNESS, ARTICULATE COLLECTIVE: DNA EVIDENCE AND THE INFERENCE OF VISIBLE TRAITS - M'charek, Amade (Bioethics, 2008)
DNA profiling is a well-established technology for use in the criminal justice system, both in courtrooms and elsewhere. The fact that DNA profiles are based on non-coding DNA and do not reveal details about the physical appearance of an individual has contributed to the acceptability of this type of evidence. Its success in criminal investigation, combined with major innovations in the field of genetics, have contributed to a change of role for this type of evidence. Nowadays DNA evidence is not merely about identification, where trace evidence is compared to a sample taken from a suspect. An ever-growing role is anticipated for DNA profiling as an investigative tool, a technique aimed at generating a suspect where there is none. One of these applications is the inference of visible traits. As this article will show, racial classifications are at the heart of this application. The Netherlands and its legal regulation of ‘externally visible traits’ will serve as an example. It will be shown that, to make this technology work, a large number of actors has to be enrolled and their articulations invited. This indicates that instead of a ‘silent witness’, a DNA profile should rather be seen as an ‘articulate collective’. Based on two cases, I argue that the normativity of visible traits is context-dependent. Taking into account the practices in which technology is put to use alerts us to novel ethical questions raised by their application.